Evaluasi Proses Bisnis Layanan Transportasi Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus: PT Citra Perdana Kendedes) - Desy Miladiana; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Citra Perdana Kendedes or better known as Citra's Taxies is a provider of transportation services in the form of taximeter cab. There are some key business processes running on company Citra Perdana Kendedes, it starts from incoming orders, shipping fleet, the auction order, pick-up and delivery orders, and service intervals. There are about 1200 incoming orders each day. However, there are hundreds of complaints coming into the company. About 70% of incoming complaints, its about the cab's delay to the customer's place. Because of these problems, it is necessary to hold the evaluation and root analysis of the problems occurred at the company. The steps that will be used in conducting the evaluation of the business process is thermally business functions using the method Value Shop Analysis, then make the models using Business Process Model and Notation (BPMN) use application of Bonita, then do mapping of Quality Factor in every business process that have been modeled using the Quality Evaluation Framework (QEF) method. 5 quality factors are produced, which are not in accordance with the company's target. The discrepancies obtained will be analyzed using 5 whys analysis method. Based on the results of the 5 whys method analysis found 22 root causes. The most root of the problem comes from the driver or human resources. This can be a reference for companies to reduce incoming complaints.